Britain's Plant Galls : A Photographic Guide - Chinery, Michael (WildGuides (Series), 2014)
This book has been produced with the aim of stimulating the general naturalist to take a closer look at the bumps and lumps that make up the fascinating world of plant galls. Induced by a variety of insects and other organisms and ranging from tiny pimples to bizarre and often very attractive and exquisitely sculptured growths, plant galls are mystery to many people, but they offer a fascinating field of study for both botanists and zoologists. Galls can be found on a very wide range of both woody and herbaceous plants, with over 50 different kinds occurring on Britain's oak trees alone, and there is still much to be learned about even the commonest examples. An introduction to the nature of plant galls and their formation; Brief descriptions of some of the organisms that cause or induce galls; Superb photographs of just over 200 of the commonest or most conspicuous of Britain's 1,000 or so plant galls, arranged according to their host plants to aid field identification; Descriptions of these galls and the life histories of the organisms that cause them.